The cellular response to ocean warming in Emiliania huxleyi - Dedman, Craig J.; Barton, Samuel; Fournier, Marjorie; Rickaby, Rosalind E. M. (Frontiers in Microbiology, 2023)
Marine phytoplankton contribute substantially to the global flux of carbon from the atmosphere to the deep ocean. Sea surface temperatures will inevitably increase in line with global climate change, altering the performance of marine phytoplankton. Differing sensitivities of photosynthesis and respiration to temperature, will shift the strength of the future oceanic carbon sink. Despite their importance, the molecular mechanisms driving these alterations in phytoplankton function remain unresolved. To address this, shotgun proteomic analysis was carried out on the coccolithophore Emiliania huxleyi following acclimation to moderate- (23°C) and elevated- (28°C) warming. Compared to the control (17°C), growth of E. huxleyi increased under elevated temperatures, with higher rates recorded under moderate- relative to elevated- warming. Proteomic analysis revealed a significant reprogramming of the E. huxleyi cellular proteome as temperatures increased: At lower temperature, cellular investment was directed towards ribosomal content, i.e. the protein factory, and photosynthetic machinery, as rates of protein translation and photosynthetic performance are restricted by low temperatures. As temperatures increased, evidence of heat stress was observed in the photosystem, characterised by a relative down-regulation of the Photosystem II oxygen evolving complex and ATP synthase. Acclimation to elevated warming (28°C) revealed a substantial alteration to carbon metabolism. Here, E. huxleyi made use of the glyoxylate cycle and succinate metabolism to optimise carbon use, maintain growth and maximise ATP production in heat-damaged mitochondria, enabling cultures to maintain growth at levels significantly higher than those recorded in the control (17°C). Based on the metabolic changes observed, we can predict that warming will benefit photosynthetic carbon fixation in the sub-optimal to optimal thermal range. Past the thermal optima, increasing rates of respiration and costs of repair will likely constrain phytoplankton growth, causing a possible decline in the oceanic carbon sink depending on the evolvability of these temperature thresholds.